Humanisme dalam Ayat-Ayat Jihad: Kajian Tafsir Al-Maraghi - Ahmad Fatih al-Faiz Binashrillah (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2024)
Humanism is a 'slippery' idea and is discussed very often in the modern world. It comes from ancient Greek and Roman roots, which then reached the phase of critical humanism in the 14th to 16th centuries, then reached its maturity in the 18th century. Islamic humanism on the other hand is far more advanced than this idea. it seeks to combine two opposing sides in man; noble and lowly; have free will and are burdened with responsibility, in order to achieve happiness in this world and the hereafter. This applies to every law of God that He revealed. The history of human liberation and liberation is ultimately the essence of the Islamic religion. Jihad, for example, is a sharia law that is often misunderstood as a doctrine of violence in the Islamic religion. He is actually much more humanistic than we think. The study of Tafsir al-Maraghi on the jihad verses in this article on the two core verses in the jihad against the polytheists has proven this. Using the library research method using Tafsir al-Maraghi as a primary source and other books as secondary sources has proven that jihad is nothing more than an effort to defend society from those who want to invade, the principle of mutual cooperation is the core of the Shari'a. On the other hand, efforts to prepare for war are the best effort to prevent war itself, as is done by developed countries in this era.